Perspektif Yuridis Praktik Paru Dheko (Kawin Lari) di Desa Ndetundora III, Kecamatan Ende, Kabupaten Ende - Maria Putri Maru; Helsina Fransiska Pello; Petornius Damat (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the juridical perspective of the practice of Paru dheko (elopement marriage) in Ndetundora III Village, Ende District, Ende Regency, particularly in relation to the fulfillment of the consensual principle in marriage and the responsibility of the male party. Paru dheko is a traditional marriage practice that still exists in society and commonly occurs due to factors such as family disapproval, economic conditions, or premarital pregnancy. This research employs an empirical legal method with a qualitative descriptive approach. Data were collected through interviews with traditional leaders, couples involved in Paru dheko, and their families, supported by secondary data from legal literature. The results indicate that the practice of Paru dheko generally fulfills the element of consensual agreement, as it is carried out based on mutual consent without coercion. However, social factors may still influence the freedom of such consent. Furthermore, the responsibility of the male party is manifested through customary processes, including acceptance of the woman, notification to her family, and the completion of customary obligations leading to the formalization of the marriage. Thus, Paru dheko can be considered valid under customary law and not contrary to positive law, provided that the elements of consent and legal responsibility are fulfilled.